The Development of Learning Strategies in Pesantren Studies on the Transformation of the Teaching System in Pesantren - Muh Mustakim (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The fundamental question of the research is how the learning strategies are developed in pesantren. follow the development of modern learning strategies or survive with his salafiah learning system. This research uses a case study. and research tends to be explanatory. Collecting data through observation, interviews and documentation. The data is taken in general, then sorted, selected, selected and reduced only in relation to the problems of this research. To maintain the validity of the data, there were three things done, namely extending the stay and interacting with respondents; make observations seriously and diligently; and tested by triangulation adopting the interactive model from Miles and Huberman. The findings from the data obtained are compiled by categories and themes, analyzed inductively conceptually and then made narrative explanations so that they are arranged into certain propositions and developed into new theories based on data analysis and narrative theoretical interpretation. The results of this research is that pesantren develop all types of learning strategies, namely direct learning strategies, learning indirect strategies, interactive learning strategies, empirical learning strategies and active learning strategies. This fact is reasonable because the education and learning process in pesantren is 24 hours. These findings indicate that pesantren accept all developments while maintaining their characteristics, so that the findings of this study lead to a theory of pesantren flexibility while maintaining their identity. The findings of this study can be continued in research on learning in certain pesantren, because it can be different from a pesantren compared to other pesantren.